A Novel NADP-Dependent Formate Dehydrogenase From the Hyperthermophilic Archaeon Thermococcus onnurineus NA1 - Yang, Ji-in; Lee, Seong Hyuk; Ryu, Ji-Young; Lee, Hyun Sook; Kang, Sung Gyun (Frontiers in Microbiology, 2022)
The genome of the hyperthermophilic archaeon Thermococcus onnurineus NA1 contains three copies of the formate dehydrogenase (FDH) gene, fdh1, fdh2, and fdh3. Previously, we reported that fdh2, clustered with genes encoding the multimeric membrane-bound hydrogenase and cation/proton antiporter, was essential for formate-dependent growth with H2 production. However, the functionality of the other two FDH-coding genes has not yet been elucidated. Herein, we purified and characterized cytoplasmic Fdh3 to understand its functionality. The purified Fdh3 was identified to be composed of a tungsten-containing catalytic subunit (Fdh3A), an NAD(P)-binding protein (Fdh3B), and two Fe-S proteins (Fdh3G1 and Fdh3G2). Fdh3 oxidized formate with specific activities of 241.7 U/mg and 77.4 U/mg using methyl viologen and NADP+ as electron acceptors, respectively. While most FDHs exhibited NAD+-dependent formate oxidation activity, the Fdh3 of T. onnurineus NA1 showed a strong preference for NADP+ over NAD+ as a cofactor. The catalytic efficiency (kcat/Km) of Fdh3 for NADP+ was measured to be 5,281 mM-1s-1, which is the highest among NADP-dependent FDHs known to date. Structural modeling suggested that Arg204 and Arg205 of Fdh3B may contribute to the stabilization of the 2-phosphate of NADP(H). Fdh3 could also use ferredoxin as an electron acceptor to oxidize formate with a specific activity of 0.83 U/mg. Furthermore, Fdh3 showed CO2 reduction activity using reduced ferredoxin or NADPH as an electron donor with a specific activity of 0.73 U/mg and 1.0 U/mg, respectively. These results suggest a functional role of Fdh3 in disposing of reducing equivalents by mediating electron transfer between formate and NAD(P)H or ferredoxin.